Mastering music at home - Mitch Gallagher (Thomson, 2008)
The final stage that puts the polished sheen on the mix. The step that allows homemade productions to better compete with those coming out of multimillion-dollar commercial recording facilities. The final preparation that will ready the music for release on CD or over the Internet. This step is called mastering. Mastering Music at Home is for any home or project studio owner or operator. It's for musicians and engineers who can't afford to pay a professional mastering engineer thousands of dollars to master their music, but who still want to get professional-level results when releasing their songs to the web or on CD. After an overview of mastering and the gear required, the book goes on to cover acoustic considerations, problem solving, distribution, and much, much more. Throughout the book, audio professionals provide additional ?in the trenches? case studies on how they approach the art of mastering. The book's companion CD-ROM includes numerous real-world music examples to help you work through the book's tutorials. This is the only guide you?ll ever need to take your home recordings to the next level